L’impact des pesticides utilisés en lutte contre le criquet pèlerin (schistocerca gregaria Forskål, 1775) (orthoptera, acrididae) sur deux espèces de pimelia (coleoptera, tenebrionidae) au Niger - Abdou Mamadou; Ahmed Mazih; Alzouma Inezdane (VertigO)
The evaluation of the impacts of chlorpyrifos ethyl and of fenitrothion on Pimelia tschadensis and Pimelia grandis mixta (Coleoptera, Tenebrionidae) was led in the valley of Tafidet (one of the summer breeding area of desert locust in Niger). The experiments were led from July to December 2004. The chemical treatments were carried out by means of an apparatus carried with hand provided with a rotary disc (MicroUlva®, Micron Sprayer Ltd, Bromyard, UK). We carried out three treatments and three repetitions according to an experimental device in complete random block. The chlorpyrifos ethyl was applied to the amount of 225 g a.i./ha; the fenitrothion with the amount of 450 g a.i./ha and a control. We used traps tubes (interception for ground arthropods) some to account for the relative abundance of the insects. The interval of time of follow-up was 94 days (4 days before treatment and 90 days after treatment). The results of this study showed that the pesticides used had a noxious effect (harmful) on the two species of Pimelia. The effects of the fenitrothion varied from 85% to 74% on P. tschadensis respectively with phases I (1-12 days) and II (16-24 days) and from 76 to 65% on P. grandis mixta with the same intervals of time. With the chlorpyrifos ethyl, these effects from 85 to 76% on P. tschadensis (phase I to phase II) and from 79 to 69% on P. grandis mixta (phase I to phase II). According to the classification of FAO, these risks are regarded as high (>75%). In phase III (28 to 90 days), the effects of the pesticides were almost non-existent with low classified risks (< 25%).